Communication of Digital Crowdfunding as a Social Behavioral Change: Systematic Literature Review of Health-Based Crowdfunding in Indonesia - Irfan, Maulana; Rusyidi, Binahayati; A Nulhaqim, Soni; Solihin, Olih (INJECT (Interdisciplinary Journal of Communication), 2026)
Health crowdfunding through digital platforms is now a major social trend in Indonesia. But how these practices correlate with Social and Behavioral Change Communication (SBCC) theories is still not widely explored. This study aims to explore the role of digital health crowdfunding within SBCC and social service delivery, especially in the Indonesian context. We used a systematic literature review method based on the PRISMA 2020 guidelines. We analyzed 45 articles published between 2015 and 2024, covering key theoretical texts on SBCC, crowdfunding, and empirical research. The findings show that Indonesian crowdfunding websites like Kitabisa.com already incorporate SBCC elements. These include agenda-setting, social norms activism, community involvement, and trust-based persuasion. This study shows a clear convergence between SBCC strategies and crowdfunding techniques. However, we also note several challenges like donor fatigue, inequality, and risks to vulnerable communities. Finally, we developed an integrated theoretical model. This model works as a heuristic tool rather than an empirical framework, which is the main theoretical contribution of this paper.